Novel snake Circovirus from alpine pit viper (Gloydius strauchi) in China: evidence of a mammal-avian genetic recombinant - Tian, Zhige; Luo, Sirong; Li, Jiayi; Liu, Xingyu; Huang, Yingxi; Fan, Yuping; Zhou, Chenlei; Guo, Peng; Hu, Xiaoliang (Frontiers in Microbiology, 2026)
IntroductionCircoviruses within the family Circoviridae have been identified across diverse vertebrate taxa, including mammals, birds, and reptiles.MethodsThis study investigated the oral cavity of the Asian pit viper (Gloydius strauchi) in southwestern China using PCR assay. The presence of Circovirus strain GsCV1 in oral samples was confirmed using PCR with consensus primers.Results and discussionIn this study, a recombinant Circovirus strain (GsCV1) was detected in the oral cavity of the Asian pit viper (Gloydius strauchi), a high-altitude species endemic to the plateaus (1,500–4,500 m) of Sichuan Province, China. Complete genome sequencing revealed a 1,811-bp circular DNA genome encoding two principal open reading frames for the replication-associated (Rep) and capsid (Cap) proteins, along with a conserved 9-bp nucleotide nonamer motif located at the apex of the stem-loop structure. Phylogenetic analysis indicated that the Rep sequence of GsCV1 clustered with mammalian circoviruses, whereas the Cap sequence was more closely related to avian strains. Recombination analysis suggested that GsCV1 emerged from interspecies recombination events involving bat-associated circovirus 3 (BatACV3), swan circovirus (SwCV), and zebra finch circovirus (ZfiCV). These findings expand the known host range and evolutionary complexity of circoviruses and raise the possibility that ecological behaviors and habitat-specific pressures in snakes may influence circoviral diversification. Further investigation is required to elucidate the prevalence, pathogenic potential, and ecological significance of circoviruses in reptilian hosts.